Inflammation induced by the new lineage of Vibrio cholerae serogroup O1 in the neonatal mouse model - Fu, Xiuping; Zhang, Jingyun; Liang, Weili; Diao, Baowei; Pang, Bo; Kan, Biao (Frontiers in Immunology, 2025)
BackgroundA novel lineage of serogroup O1 El Tor V. cholerae, genetically distinct from the seventh pandemic strain, has recently been identified in China and linked to diarrheal outbreaks. Investigations were conducted to examine the inflammation in the intestines of mice infected with V. cholerae strains including the new lineage strains VC6050 (ctxAB +) and VC6055 (ctxAB -), as well as the seventh pandemic strains of V. cholerae N16961.ResultsThe result showed that the colonization abilities of V. cholerae in the intestines of mice infected with VC6050 and N16961 was significantly higher than that of the VC6055 group. Histological sections of the small intestine revealed a few inflammatory cell infiltrations in the muscularismucosa, with inflammation being the primary form of tissue damage. The transcript changes in the neonatal mouse intestine were primarily associated with immune and inflammation-related genes after V. cholerae infection, including CCL7, CCL17, CCL21, CXCL9, and CXCL10. In comparison to the seventh pandemic strain N16961, the new lineage strains exhibited significant up-regulation of carboxyesterase and genes involved in aquaporin-mediated transport, whereas some inflammation-related genes were down-regulated. When compared to the nontoxigenic strain VC6055, the toxigenic strains N16961 and VC6050 demonstrated significant up-regulation of inflammation related genes and alpha-defensin gene (Defa). Conclusions: The results suggest that, in comparison to the seventh pandemic strains of V. cholerae, the new lineage strains exhibit lower levels of inflammatory cytokines and chemokines. Furthermore, CTX-positive strains, when contrasted with CTX-negative strains, not only activate a greater number of inflammatory factors but also stimulate the host to generate more antimicrobial peptides.